Экспериментальная оценка условий запуска гидровращательного бурового снаряда погружной установки УГПВ-150 - Зыбинский, П.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
On the basis of the analysis of experimental datas got in case of research of work of hydraulic drills executed on base piston hydraulic with the valvular distribution of fluid is selected to the appropriateness of forming the start conditions for different combinations of structural elements conditioned by the specific character of exploitation of hydraulic drills with the complement of the setting UGVP-150.